Biphasic hydroformylation of 1,4-diacetoxy-2-butene: a kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 1,4-diacetoxy-2-butene was studied using a water-soluble Rh complex catalyst prepared in situ from [Rh(COD)Cl](2) complex and trisodium salt of tri-(m-sulfophenyl)phosphine (TPPTS) in a biphasic system. The sequence of addition of catalyst precursor, ligand, and reactant/solvent showed a significant effect on leaching of Rh from aqueous to organic phase, and hence, the procedure was optimized to develop a nonleaching and stable biphasic catalyst system. The only hydroformylation product (1,4-diacetoxy-2-formyl butane, DAFB) formed was found to deacetoxylate completely to 2-formyl-4-acetoxybutene (FAB), thus allowing a one-pot synthesis of FAB, an important intermediate for Vitamin A. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained, and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst concentration were studied in a stirred batch reactor over a temperature range of 338-358 K. The effect of aqueous phase holdup on the initial rate of hydroformylation and analysis of gas-liquid and liquid-liquid mass transfer effects were also investigated to identify the reaction rate data operating in a kinetic regime. A rate equation based on the known hydroformylation reaction mechanism was used to fit the experimental rate data and to evaluate kinetic parameters. The agreement between the model prediction and the experimental data was found to be excellent. The activation energy was calculated as 30.1 kJ/mol. The biphasic catalyst system reported here is not only efficient for catalyst-product separation but also provides a tandem synthesis of Vitamin A intermediate, FAB.